Immunotherapy in triple-negative breast cancer: Insights into tumor immune landscape and therapeutic opportunities - Ribeiro, Rita; Carvalho, Maria João; Goncalves, João; Moreira, João Nuno (Frontiers in Molecular Biosciences, 2022)
Triple-Negative Breast Cancer (TNBC) is a clinically aggressive subtype of breast cancer that represents 15-20% of breast tumors and is more prevalent in young pre-menopausal women. It is the subtype of breast cancers more associated with metastization and recurrence at the first 5 years after diagnosis, and presents higher mortality when pathological complete response is not achieved. As TNBC cells lack estrogen, progesterone and HER2 receptors, patients do not respond well to hormone and anti-HER2 therapies, and conventional chemotherapy remains the standard treatment. Despite efforts to develop targeted therapies, it remains a disease with high unmet medical need and urgent demand for customized diagnosis and therapeutics. As immunotherapy is changing the paradigm of anticancer treatment, it arises as an alternative for the treatment of TNBC patients. TNBC is an immunogenic subtype of breast cancer, due to its high levels of tumor mutational burden and presence of immune cell infiltrates. This review addresses its implication in the diagnosis, treatment and prognosis of the disease. Herein, the role of immune gene signatures and tumor infiltrating lymphocytes as biomarkers in TNBC is reviewed, aiming at their application in patient diagnosis and stratification, as well as predictors of therapy response. PD-L1 expression is already used as predictive of response to checkpoint inhibitor therapy, but challenges regarding its value as biomarker will be described. Moreover, the rationale of different formats of immunotherapy under clinical research against TNBC is discussed, and major clinical trials are highlighted. Immune checkpoint inhibitors have demonstrated clinical benefit, particularly in early-stage tumors and when administered in combination with chemotherapy, with several regimens approved by the regulatory authorities. Antibody-drug conjugates success and research on other emerging approaches, such as vaccines and cell therapy are also addressed. These advances give hope on the development of personalized, more effective and safe treatments, which will improve the survival and quality of life of patients with TNBC.